PENGEMBANGAN PARIWISATA KAWASAN BATURRADEN - Naufal Kresna Diwangkara; Suzanna Ratih Sari; R. Siti Rukayah (Jurnal Arsitektur ARCADE, 2020)
Abstract: The tourism industry in the Baturraden area, can be said to be one of the most popular tourism industries in Banyumas Regency. Judging from the number of visitors, in 2017 even visitors visiting the Baturraden tourist area can be considered quite large, namely a number of 633,420 visitors where an increase of 4.86% from the previous year. The development of tourism around the Baturraden area also experienced changes along with the development of the main tourism area, namely Baturraden tourism. The spatial layout of this region also indirectly changes following the existing tourism patterns, especially areas that are in direct contact with the tourism area. Therefore, this study wants to identify the condition of the Baturraden tourist area seen from 4 indicators namely (Attraction, Amenity, Accessibility, Ancillary) in order to find out the extent to which the Baturraden tourism area has been prepared to accommodate tourist visitors who come by looking at the application of the four indicators. in the field. The method used in this research is a qualitative method with the process of finding data that is done by way of direct surveys to the field, interviews, and literature studies through books, research journals and related through internet pages. The final results of this study in the form of exposure to the identification of Baturraden Tourism area seen from 4 factors, namely Attraction, Amenity, Accessibility, and Ancillary.Keyword: Kata Baturraden Tourism Area, Baturraden Spatial Planning, Identification 4A. Abstrak: Industri pariwisata di kawasan Baturraden, dapat dikatakan sebagai salah satu industri pariwisata yang paling banyak diminati di Kabupaten Banyumas. Dilihat dari jumlah pengunjungnya, pada tahun 2017 bahkan pengunjung yang mengunjungi kawasan wisata Baturraden dapat dibilang cukup besar yaitu sejumlah 633.420 pengunjung dimana terjadi peningkatan 4,86% dari tahun sebelumnya. Perkembangan wisata disekitaran kawasan Baturraden pun turut mengalami perubahan seiring berkembangnya kawasan pariwisata induk yaitu lokawisata Baturraden. Tata ruang kawasan ini pun secara tidak langsung ikut berubah mengikuti pola pariwisata yang ada, terutama daerah yang bersinggungan langsung dengan kawasan pariwisata. Maka dari itu, penelitian ini hendak mengidentifikasi kondisi kawasan wisata Baturraden dilihat dari 4 indikator yaitu (Attraction, Amenity, Accessibility, Ancilliary) dengan tujuan untuk mengetahui sejauh mana kawasan pariwisata Baturraden sudah disiapkan untuk mengakomodir pengunjung wisata yang datang dengan melihat pengaplikasian ke empat indikator tersebut di lapangan. Metode yang digunakan dalam penelitian ini yaitu metode kualitatif dengan proses pencarian data yang dilakukan dengan cara survey langsung ke lapangan, wawancara, dan studi literatur melalui buku, jurnal penelitian terkait maupun melalui halaman internet. Hasil akhir penelitian ini berupa paparan identifikasi kawasan Pariwisata Baturraden dilihat dari 4 faktor yaitu Attraction, Amenity, Accessibility, dan Ancilliary.Kata Kunci: Kawasan Wisata Baturraden, Tata Ruang Baturraden, Identifikasi 4A.